Diversity Management in Classroom: Exploration of Teacher's Role (Patan Pragya, 2020)
Nepal is a country of diversity in terms of ideological, cultural, religious, caste, geographical and sexual orientation, ethnicity, class and language. Diversity is not merely a problem, it is an opportunity for exploring creativity of individuals who have cultural, racial, and ethnic differences. In this context, this study aims to explore the role of teacher in diversity management in the classroom. I chose purposive sampling to identify the participant for my study. Headteacher, teacher and the students are the participant in my study. Multicultural education, Fair treatment and respect of differences are key for living diversity. Differences of the individuals need to addressed inside and outside the classroom. Diversity is the property of the school from which teacher and students learn different idea information and knowledge form the diversified students in his school. Diversity need to celebrate in the school in the different functions.